A Preliminary Review of Modified Polymethyl Methacrylate and Calcium-Based Bone Cement for Improving Properties in Osteoporotic Vertebral Compression Fractures - Gong, Yining; Zhang, Bo; Yan, Liang (Frontiers in Materials, 2022)
The incidence of osteoporotic vertebral compression fractures (OVCFs) increases gradually with age, resulting in different degrees of pain for patients, even possible neurological damage and deformity, which can seriously affect their quality of life. Vertebral augmentation plays an important role in the surgical treatment of OVCFs. As the most widely used bone cement material, polymethyl methacrylate (PMMA) offers inherent advantages, such as injectability, ease of handling, and cost-effectiveness. However, with its application in the clinic, some disadvantages have been found, including cytotoxicity, high polymerization temperature, high elastic modulus, and high compressive strength. To improve the mechanical properties and the biological performance of conventional PMMA bone cement, several studies have modified it by adding bioceramics, bioglass, polymer materials, nanomaterials, and other materials, which have exhibited some advantages. In addition, other alternative materials, such as calcium phosphate, calcium sulfate, and calcium silicate cements—including their modifications—have also been explored. In this review, we examined the existing research on the side-effects of conventional PMMA bone cement, modified PMMA bone cement, and other alternative materials designed to improve properties in OVCFs. A overview of various modified bone cements can help further scientific research and clinical applications.